School of belonging an agroeco-generative secondary educational complex for place-based Lumad learning - Gonzalbo, Jean Edsel M.; Gines, Leonido Jr. M. (Quezon City College of Architecture, University of the Philippines Diliman, 2024)
For the Lumad, land is life. Amid their struggle for genuine land ownership vis-a-vis the continuous political conflict in Mindanao, the Lumad children face disenfranchisement—pushed to either enter mainstream schools, or create community-led schools for themselves. The former is equipped with better facilities, but they do not conform with the cultural, and sociopolitical nuances that a Lumad curriculum requires. On the other hand, the alternative Lumad classrooms are community-driven making it more accurate in delivering the right Lumad education, but they are spatially inadequate. Additionally, none of these community-led schools are now in operation due to forced closure.

Hence, this study architecturally addresses the gap between the limitations of mainstream schools in providing a context-sensitive curriculum, and the spatial inadequacy of the community-led schools. It proposes solutions in the form of a holistic secondary educational complex that will capture the core aspects of the unique Lumad curriculum, provide a setting for agroecology and conducive place-based learning, while simultaneously serving as a space of sanctuary. It aims to determine architectural strategies for integrating the agroecological element of the Lumad curriculum into the facility. This study utilizes a qualitative research method through vernacular mapping, key informant interview, and secondary data analysis to lay the knowledge foundations of the research.

Finally, through the agroeco-generative aspect in its design, the school complex will generate tangible and intangible agroeco-outcomes in the promotion of serving the underserved Lumad children.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Agricultural ecology; High school facilities -- Designs -- Mindanao